Protocol for a double-blind placebo-controlled trial to evaluate the efficacy of probiotics in reducing antibiotics for infection in care home residents: the Probiotics to Reduce Infections iN CarE home reSidentS (PRINCESS) trial. Issue 6 (20th June 2019) - Owen-Jones, Eleri; Lowe, Rachel; Lown, Mark; Gillespie, David; Addison, Katy; Bayer, Tony; Calder, Philip C; Davies, Jane; Davoudianfar, Mina; Downs, James; Edwards, Alison; Francis, Nick A; et al.
Abstract : Introduction: Care home residents are at increased risk of infections and antibiotic prescription. Reduced antibiotic use from fewer infections would improve quality of life. The P robiotics to R educe I nfections i N C ar E home re S ident S (PRINCESS) trial aims to determine the efficacy and investigate mechanisms of daily probiotics on antibiotic use and incidence of infections in care home residents. Methods and analysis: PRINCESS is a double-blind, individually randomised, placebo-controlled trial that will assess the effect of a daily oral probiotic combination of Lactobacillus rhamnosus, GG (LGG) and Bifidobacterium animalis subsp. lactis, BB-12 (BB-12) on cumulative antibiotic administration days (CAADs) (primary outcome) for infection in up to 330 care home residents aged ≥65 years over up to 12 months. Secondary outcomes include: Infection: Total number of days of antibiotic administration for each infection type (respiratory tract infection, urinary tract infection, gastrointestinal infection, unexplained fever and other); number, site, duration of infection; estimation of incidence and duration of diarrhoea and antibiotic-associated diarrhoea; Stool microbiology : Clostridium difficile infection; Gram-negative Enterobacteriaceae and vancomycin-resistant enterococci; LGG and BB-12. Oral microbiology: Candida spp. Health and well-being: Self and/or proxy health-related quality of life EQ5D (5 L); self-and/or proxy-reported ICEpop CAPability measure for older people. Hospitalisations: number and duration of all-cause hospital stays. Mortality: deaths. Mechanistic immunology outcomes: influenza vaccine efficacy (haemagglutination inhibition assay and antibody titres); full blood count and immune cell phenotypes, plasma cytokines and chemokines; cytokine and chemokine response in whole blood stimulated ex vivo by toll-like receptor 2 and 4 agonists; monocyte and neutrophil phagocytosis of Escherichia coli ; serum vitamin D. Ethics and dissemination: Ethics approval is from the Wales Research Ethics Committee 3. Findings will be disseminated through peer-reviewed journals and conferences; results will be of interest to patient and policy stakeholders. Trial registration number: ISRCTN16392920 ; Pre-results.